2010
DOI: 10.2460/ajvr.71.7.840
|View full text |Cite
|
Sign up to set email alerts
|

Renal and cardiorespiratory effects of treatment with lactated Ringer's solution or physiologic saline (0.9% NaCl) solution in cats with experimentally induced urethral obstruction

Abstract: Treatment with LRS or PSS appeared to be safe and effective in cats with experimentally induced UO; however, LRS was more efficient in restoring the acid-base and electrolyte balance in severely decompensated cats with UO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 27 publications
0
16
1
2
Order By: Relevance
“…One study comparing 0.9% NaCl and a balanced electrolyte solution (Normosol R) in clinical UO patients showed no difference in outcome (survival, length of stay) or in reduction of serum potassium concentrations, though acid–base abnormalities corrected more rapidly in the Normosol R group . Another study used a model of experimentally induced feline UO to create a more uniformly and severely affected population (mean BUN of 99.2 mmol/L [278 mg/dL], creatinine of 663 μmol/L [7.5 mg/dL] versus BUN of 14.3–17.9 mmol/L [40–50 mg/dL], creatinine of 247.5–318.2 μmol/L [2.8–3.6 mg/dL] in the previous study) to compare administration of 0.9% NaCl versus lactated Ringer's solution . Similarly, this study found more rapid improvement of acid–base values with lactated Ringer's, but no difference in clinical outcome, decrease in potassium, or decrease in renal values.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…One study comparing 0.9% NaCl and a balanced electrolyte solution (Normosol R) in clinical UO patients showed no difference in outcome (survival, length of stay) or in reduction of serum potassium concentrations, though acid–base abnormalities corrected more rapidly in the Normosol R group . Another study used a model of experimentally induced feline UO to create a more uniformly and severely affected population (mean BUN of 99.2 mmol/L [278 mg/dL], creatinine of 663 μmol/L [7.5 mg/dL] versus BUN of 14.3–17.9 mmol/L [40–50 mg/dL], creatinine of 247.5–318.2 μmol/L [2.8–3.6 mg/dL] in the previous study) to compare administration of 0.9% NaCl versus lactated Ringer's solution . Similarly, this study found more rapid improvement of acid–base values with lactated Ringer's, but no difference in clinical outcome, decrease in potassium, or decrease in renal values.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…Although some clinicians use 0.9% NaCl to avoid administering potassium, it is clear that more balanced electrolyte solutions (lactated Ringer's, Normasol R) allow for a more rapid correction of acid-base status without affecting normalization of serum potassium levels. 69,70 In cases of marked hyperkalemia, calcium gluconate (a functional antagonist of potassium) should be administered slowly, intravenously (0.5 mL/kg). Although it does not lower serum potassium, calcium changes the threshold potential and returns membrane excitability to normal for approximately 20 to 30 minutes.…”
Section: Uroperitoneummentioning
confidence: 99%
“…This study was a pilot study from two other studies [8,9]. Fifteen neutered male adult mixed breed cats (weight range 3 to 5 kg) were housed in individual cages, fed dry commercial food and water was available ad libitum.…”
Section: Open Access Short Communicationmentioning
confidence: 99%
“…The animals were submitted to a urethral obstruction model [8,9] (parallel study) and submitted to the anesthetic for relieving of urethral obstruction when any 3 of 4 clinic pathologic criteria were met: venous pH < 7.2, BUN concentration > 200 mg/ dL, serum creatinine concentration > 4.5 mg/ dL, and serum potassium concentration > 6.5 mEq/ L.…”
Section: Open Access Short Communicationmentioning
confidence: 99%
See 1 more Smart Citation